INVOLVEMENT OF THE FIRST-YEAR SCHOOL STUDENTS’ FAMILY INTO THE COMMUNITY OF EXTENDED DAY GROUP - Kardelienė, Laimutė (Acta Paedagogica Vilnensia, 2009)
It can be stated that the relationship between teachers and parents/ children’s legal guardians is also the relationship of mutual learning. The article makes the onclusions that unitedness and differentiation from the school community of the first-form students attending the extended day group primarily indicates the positive attitude of the mothers surveyed towards the education of a child when organizing his / her activities promoting academic, physical development and social self-respect. However, only a minor part of the resdpondents were involved into the activity of the extended day group due to the lack of adequate information; besides, they rarely participate in the process of decision taking there. The involvement of the first-year students into the school community is based on children’s academic activities within the extended day group promoting reading, writing and calculation skills. Besides, in order to take care of the efficiency of the social net student – parents – school, it is essential to respond to the parents’ Įteikta: 2008 09 15 Priimta: 2009 03 09need of ensuring their children’s safety and full-scale occupation after lessons.
Keywords: the first-year school student’s family; involvement; community; first-year school student’s self-esteem